2015
DOI: 10.1371/journal.pone.0141984
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tellurite Resistance Operon in Filamentous Growth of Yersinia pestis in Macrophages

Abstract: Background Yersinia pestis initiates infection by parasitism of host macrophages. In response to macrophage infections, intracellular Y. pestis can assume a filamentous cellular morphology which may mediate resistance to host cell innate immune responses. We previously observed the expression of Y. pestis tellurite resistance proteins TerD and TerE from the terZABCDE operon during macrophage infections. Others have observed a filamentous response associated with expression of tellurite resistance operon in Esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…We found P0 ancestor had gained different types of metabolic genes compared to the phylogroup-E species. It gained tellurite resistance genes ( ter ZABCD) and itaconate catabolic genes ( rip ABC), which had been shown by previous studies as adaptive strategies to survive inside macrophages282930. Besides, P0 ancestor had gained several virulence genes, including pil WVUSRQPONML (type IV pilus gene cluster which resides in Yersinia adhesion pathogenicity island), psa ABCEF (pH 6 antigen genes).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We found P0 ancestor had gained different types of metabolic genes compared to the phylogroup-E species. It gained tellurite resistance genes ( ter ZABCD) and itaconate catabolic genes ( rip ABC), which had been shown by previous studies as adaptive strategies to survive inside macrophages282930. Besides, P0 ancestor had gained several virulence genes, including pil WVUSRQPONML (type IV pilus gene cluster which resides in Yersinia adhesion pathogenicity island), psa ABCEF (pH 6 antigen genes).…”
Section: Resultsmentioning
confidence: 98%
“…We found that the phylogroup-P species seemed to have expanded their ecological niche to macrophages, probably due to the acquisition of putative genes such as ter and rip loci, and the loss of two cellulose biosynthesis loci ( bcs ), which could also increase virulence inside the macrophages28293033. This might allow the phylogroup-P species to occupy the macrophage compared to its predecessor and phylogroup-E, which usually adapt to the intestinal tracts.…”
Section: Discussionmentioning
confidence: 96%
“…30 Tellurite resistance is needed to colonize macrophages. 31 The TerABCDEWXYZ proteins cluster was identified in 12.9% (4/31) and 12.5% (1/8), of K. variicola and K. quasipneumoniae, all of human origin. K. variicola 8917 isolate was described as hypermucoviscous.…”
Section: In Silico Analysis and Prevalence Of Fimbrial Fimv Proteinmentioning
confidence: 98%
“…Thus terZABCDEF, terZABCDE and TerABD present in E. coli O157:H7, Proteus sp. and D. radiodurans, respectively, are operons (Makarova et al, 2001;Ponnusamy and Clinkenbeard, 2015;Taylor et al, 2002). The Psychrobacter genus represents an exception to this rule, with terA lying in the opposite transcriptional orientation ( Supplementary Figure 1).…”
Section: Discussionmentioning
confidence: 99%